2017
DOI: 10.3390/s17122792
|View full text |Cite
|
Sign up to set email alerts
|

Repetitively Mode-Locked Cavity-Enhanced Absorption Spectroscopy (RML-CEAS) for Near-Infrared Gas Sensing

Abstract: A Pound-Drever-Hall (PDH)-based mode-locked cavity-enhanced sensor system was developed using a distributed feedback diode laser centered at 1.53 µm as the laser source. Laser temperature scanning, bias control of the piezoelectric ceramic transducer (PZT) and proportional-integral-derivative (PID) feedback control of diode laser current were used to repetitively lock the laser modes to the cavity modes. A gas absorption spectrum was obtained by using a series of absorption data from the discrete mode-locked p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A minimum detection limit of 104.9 ppmv for an average time of 50 s was attained by observing the absorption of water vapor. 18 In 2020, He et al further demonstrated a formaldehyde (H 2 CO) detection system involving a continuous-wave distributed feedback interband cascade laser with a wavelength of 3.6 μm and an assembly F-P cavity with 20 m effective optical path. A minimum detection limit of 5.8 ppbv for an average time of 30 s was attained by observing the absorption of H 2 CO. 19 ML-CEAS has promising potential for gas detection application, however, there are limitations to high-precision but expensive and bulky PDH mode-locking devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimum detection limit of 104.9 ppmv for an average time of 50 s was attained by observing the absorption of water vapor. 18 In 2020, He et al further demonstrated a formaldehyde (H 2 CO) detection system involving a continuous-wave distributed feedback interband cascade laser with a wavelength of 3.6 μm and an assembly F-P cavity with 20 m effective optical path. A minimum detection limit of 5.8 ppbv for an average time of 30 s was attained by observing the absorption of H 2 CO. 19 ML-CEAS has promising potential for gas detection application, however, there are limitations to high-precision but expensive and bulky PDH mode-locking devices.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, He et al locked a distributed feedback laser diode with a central wavelength of 1.53 μm to the fundamental mode (TEM 00 mode) of an F‐P cavity with an optical path of 49.7 m based on the Pound–Drever–Hall (PDH) technique. A minimum detection limit of 104.9 ppmv for an average time of 50 s was attained by observing the absorption of water vapor 18 . In 2020, He et al further demonstrated a formaldehyde (H 2 CO) detection system involving a continuous‐wave distributed feedback interband cascade laser with a wavelength of 3.6 μm and an assembly F‐P cavity with 20 m effective optical path.…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared (NIR) light often defined in the wavelength range of 800 to 2500 nm is transparent in many materials and has been widely used in optical telecommunication, face recognition, , autonomous driving, gas sensing, bioimaging, and so on. Conventional silicon (Si) photodetectors have sensitivity up to ∼1100 nm, and longer wavelength ranges are covered by narrow band gap semiconductors such as InGaAs, InP, and Ge.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-pass gas cell [10] and a high-fineness cavity [11] are two kinds of gas absorption approaches for enhancing sensitivity based on different principles, which are widely used in TDLAS based gas sensor systems. A multi-pass cell realized by symmetric spherical mirrors in a Herriott cell configuration is commonly used for trace-gas detection [12][13][14], in Raman spectroscopy [15][16] and atmospheric in situ instrumentation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%